De cirkel. - Coessens, Piet (s.l. : Roger Raveelmuseum, 2007)
Raveel, Roger ; Henning, Anton ; Appel, Karel ; Kahrs, Johannes ; Dumas, Marlène ; De Keyser, Raoul ; Ryman, Cordy ; Förg, Günther ; Wyckaert, Maurice ; Alechinsky, Pierre ; Daniëls, René ; Bujnowski, Rafat ; Knoebl, Imi ; Elsner, Slawomir ; Lueg, Konrad ; Schoonoven, Jan ; Kobayashi, Masato
De cirkel, Roger Raveelmuseum, Machelen-aan-de-Leie, 25 maart - 20 mei 2007
boek